2023
DOI: 10.1002/hyp.14864
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality reduction for regional flood frequency analysis: Linear versus nonlinear methods

Abstract: Regional flood frequency analysis is still an important area of hydrology research as there are many ungauged catchments. The majority of hydrological methods in regional flood frequency analysis involve complex non‐linear relationships between predictor variables and flood characteristics. In the past, dimensionality reduction techniques based on linear methods such as canonical correlation analysis (CCA) were used in regional flood frequency analysis to delineate hydrological clusters. Non‐linear dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Comparative analyses revealed that the PCA-SOM-NARX framework demonstrated superior predictive outcomes relative to the SOM-NARX baseline, highlighting the pivotal role of PCA in enhancing prediction efficacy. Additionally, Haddad and Rahman [45] employed both linear DR techniques, specifically canonical correlation analysis (CCA), and non-linear methods, notably MDS and kernel CCA, for regional flood frequency analysis. The empirical results of their research illustrated that non-linear methodologies yielded superior performance over their linear counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Comparative analyses revealed that the PCA-SOM-NARX framework demonstrated superior predictive outcomes relative to the SOM-NARX baseline, highlighting the pivotal role of PCA in enhancing prediction efficacy. Additionally, Haddad and Rahman [45] employed both linear DR techniques, specifically canonical correlation analysis (CCA), and non-linear methods, notably MDS and kernel CCA, for regional flood frequency analysis. The empirical results of their research illustrated that non-linear methodologies yielded superior performance over their linear counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%